RESEARCH ON SPEECH ACTS IN UZBEK LINGUISTICS: METHODS AND APPROACHES (Scientific journal of the Fergana State University, 2025)
This article discusses the theory of speech acts, which is currently relevant in Uzbek linguistics, as well as acts and approaches to it. The study of speech acts as a separate research topic in world and Uzbek linguistics indicates its great importance in linguistics. It should be noted that the methods used in the linguistic analysis of speech acts play an important role in developing clear criteria for their classification and revealing context-based approaches. Existing methods and approaches in the study of speech acts play a key role in revealing its fundamental essence. The novelty that emerged as a unique approach in the article is the study of the interrelationship of these speech acts with the science of psycholinguistics. Through this integrative approach, the relationship between them: the role of the human psyche in the formation of a speech act, which part of the human brain is responsible for speech acts, the direct impact of speech disorders on speech acts, etc, is formed in a field where the two fields are combined. The study of speech acts within the framework of linguistics opens up new ways of modeling language.